PERBEDAAN MODEL PEMBELAJARAN PBL DAN MODEL PEMBELAJARAN PBI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA PADA MATERI SPLTV KELAS X SMA NEGERI 8 MEDAN T.P 2019/2020 - Enjelina, Dina Kristina (LPPM Universitas HKBP Nommensen, 2025)
This research is a quasi-experimental type of research. Population is the whole object in which there are subjects that can be used as a source of data that is expected to provide the data needed by researchers. The population in this study were X MIA class students at SMA Negeri 8 Medan. The technique that will be used in this sampling is using Purpossive sampling technique. The purpose of pseudo research is to obtain information that is an approximation for information that can be obtained with actual experiments in circumstances where it is impossible to control and manipulate all relevant variables. The results showed that the design of the learning model that had been designed was good to use. From the calculation obtained tcount = 1.71 and ttable = 1.670 It turns out that tcount = 1.71> ttable = 1.670 so that Ha is accepted or H0 is accepted, it can be concluded that the final ability of students taught using PBI learning model is better than students taught with PBL learning model on students' mathematical communication skills.